Global Activism In The Governance Of Gender-Responsive Policies At Cop 28 In 2023 - Siti Ghefira Naila; Nuraeni Nuraeni (UNIVERSITAS PAKUAN, 2026)
Climate change is not only an environmental issue but also closely linked to social inequality, including gender inequality. In the context of global climate governance, gender mainstreaming has become a crucial approach to ensuring that climate policies are responsive to the needs of groups disproportionately affected by the climate crisis. This research aims to analyze the role of global activism in promoting the integration of gender-responsive policies into international climate governance processes, particularly at the COP 28. COP 28, held in Dubai, marked an important momentum for strengthening gender-responsive policies in global climate negotiations. This was reflected in the introduction of the first-ever Gender Day and the launch of the Gender-Responsive Just Transitions and Climate Action Partnership, both of which emphasized the importance of equitable and inclusive energy transitions. Within the broader international policy framework, the integration of gender perspectives is further supported by instruments such as the Gender Action Plan (GAP) under the United Nations Framework Convention on Climate Change, as well as gender-sensitive funding mechanisms through the Green Climate Fund. Moreover, the integration of gender perspectives in global climate governance increasingly adopts an intersectional approach. This approach recognizes that vulnerability to climate change is shaped not only by gender but also by other factors such as social class, ethnicity, geographic location, and economic status. Through an analysis of policy dynamics and practices emerging from COP 28, this study seeks to examine how pressure and advocacy from global activist actors contribute to strengthening gender-responsive climate policies. In addition, it aims to explore the relationship between global activism and the development of more inclusive international climate policies within the framework of global climate governance.